The Influence of Permissive Parenting Style and Religiosity on the Intensity of Worship of Adolescents in IB Hamlet, Klambir Village, Lima Kampung - Rozy, Fahrur; Sinaga, Ali Imran; Haidir, Haidir (Electronic Journal of Education, Social Economics and Technology, 2024)
Nowadays, the intensity of adolescent worship is closely related to the parenting style given by parents, and the emergence of religious attitudes in adolescents. Where, the parenting style, especially permissive, parents free their children or spoil their children too much. Furthermore, religiosity is interpreted as a form of obedience and love for Allah SWT. After conducting observations in Dusun IB, Klambir Village, Lima Kampung, a problem was found, namely the low intensity of adolescent worship, especially related to congregational dawn prayers. This study aims to describe; 1) The effect of permissive parenting style on the intensity of adolescent worship in Dusun IB, Klambir Village, Lima Kampung, 2) The effect of religiosity on the intensity of adolescent worship in Dusun IB, Klambir Village, Lima Kampung, 3) The effect of permissive parenting style and religiosity on the intensity of adolescent worship in Dusun IB, Klambir Village, Lima Kampung, Hamparan Perak District. This research method is a quantitative method with a correlation approach, or multiple correlation (X1, X2, Y). The population of this study was 147 adolescents and the sample of this study was 30 adolescents. The results of this study revealed that ; 1) Permissive parenting style has an influence on the intensity of adolescent worship in Dusun IB, Klambir Lima Village, by 23.1% with a low correlation. 2) Religiosity has an influence on the intensity of adolescent worship in Dusun IB, Klambir Lima Village, by 20.4% with a low correlation. 3) Permissive parenting style and religiosity together have an influence on the intensity of adolescent worship in Dusun IB, Klambir Lima Village, Hamparan Perak District by 42.0% with a moderate correlation.